Relação / controle populacional de cães e gatos / melhoria das condições ambientais e bem-estar da comunidade no bairro da Paupina em Fortaleza - Ceará - Faria, Janalia Azevedo de (2014)
The interaction between man and pets has grown substantially bringing very benefits to the health population, however in this coexistence is not free of injuries when this relationship does not occur in a responsible manner. Among the complications caused by the lack of proper management of these animals are severe diseases that can be transmitted to humans, addition to aggressions, traffic accidents, pollution from dejections, noise pollution and other perturbations. This work aims to control the feline and canine populations by the surgical method, relating to the responsible pet ownership, bringing improvements in environmental and well being conditions in the community in the neighborhood Paupina, Fortaleza-CE. Being realized a questionnaire with neighborhood residents, both those created as those not created pets. Doing raising of existing zoonoses, discomfort and disorders caused by animals, performing guidelines on responsible pet ownership, and making registration of breeders of dogs and cats, for performing the surgical sterilization. After six months of the completed the castrations, the same questionnaire was reapplied to make comparison of data before and after castration. In the first phase of the survey questionnaire was conducted with 410 residents, and created 199 of these dogs and/or cats, in a total of 366 animals. 69 % of dogs and 95 % of cats have never had service veterinarian, but despite the low attendance 88 % of dogs were vaccinated with some kind of vaccine that cats only 48 %. It was reported by 91.7 % of respondents, the presence of animals that roam freely in the streets, and 62 % said that the animals had owners, but free access to the street. The existence of faeces and trash from stray animals account for more than 60 % of the responses and the most common zoonosis in the community was the larva migrans, representing 62 % of people who have had some kind of zoonosis .Being reported by most troublesome residents and disorders by vocalizations and conglomerates dogs in estrus period of females. Factor compounded by the low rate of castrations , only 2 % of dogs and 9 % of cats were neutered , however there was wide acceptance of surgery , castration was performed in 208 animals , representing 91 % of the owners who wished to neuter their animals . After this procedure in comparing the data, it can be observed reduction in the dropout rate, vocalization, worning, trampling and the number of stray animals on the streets . We can conclude that in the neighborhood Paupina with basic animal care is not taken, there is no adequate vaccination, worming and veterinary medical care. Not responsible ownership, which brings diseases society being held. And preventive measures to control the population of animals, the surgical method, reduce injuries and discomfort to the environment and society . Resulting in a more harmonious environment between men and animals, and to be preserved must raise awareness of the risks and required with pet care